Analysis of the Implementation of Kaizen Culture at PT. Digital Solusi Grup - Putra, Novaldi Nur Rochman; Sukarno, Gendut; Pertiwi, Tri Kartika (International Journal of Business and Applied Economics, 2024)
This study aims to examine the implementation of Kaizen culture in the company. The discussion is based on the phenomenon of Kaizen culture implementation originating from Japan, applied to a service sector company in Indonesia, namely PT Digital Solusi Grup. The objectives of this study are to determine (1) how the Kaizen culture is implemented in the company, and (2) whether the implementation of the system, concept, and Gemba Kaizen in the company undergoes adaptation. This research adopts a descriptive qualitative approach using ethnographic methods. Data collection techniques include in-depth interviews, documentation, observation, and triangulation. The components of data analysis in this study are (1) data reduction, (2) data presentation, and (3) drawing conclusions. The main discussion focuses on (1) the Kaizen culture in the company, and (2) the adaptation of Kaizen culture, which includes the concepts and Gemba Kaizen. Information for this study was gathered from three key informants representing top-level, middle-level, and first-level management at PT Digital Solusi Grup. The findings of this study indicate that, in general, the implementation of Kaizen culture undergoes an adaptation process. A lack of communication during the implementation process between functions and positions prevents the company's goals for implementing Kaizen culture from being articulated in accordance with the leadership's objectives.